THE EFFECT OF ECONOMIC VALUE ADDED (EVA), MARKET VALUE ADDED (MVA), LIQUIDITY, AND LEVERAGE ON STOCK PRICES - Trisandi Eka Putri; Icih Icih; Nolis Putri Indriyani (Sekolah Tinggi Ilmu Ekonomi Sutaatmadja, 2025)
Stock prices are prices that occur on the exchange at a certain time. Stock prices can change up or down in a matter of time so quickly. This is possible because it depends on demand and supply between stock buyers and stock sellers The purpose of this study is to determine the effect of Economic Value Added (EVA), Market Value Added (MVA), Liquidity, and Leverage on Stock Price. The population in this study is, Companies in the sub-sector of the material, component and equipment industry listed on Bursa Malaysia and Indonesia Stock Exchange for the period 2019 – 2022. This type of research is quantitative research. With purposive sampling method. Data analysis techniques in this study use descriptive analysis, classical assumption tests, multiple regression analysis, and hypothesis tests. The results of this study show that Economic Value Added (EVA), liquidity, and leverage has a significant positive effect on stock prices, while Market Value Added (MVA) do not affect stock prices.